VIBRATION ANALYSIS OF TIMOSHENKO BEAM SUBJECTED TO PARTIALLY DISTRIBUTED MOVING LOAD (FULafia Journal of Science and Technology, 2020)
Vibration analysis of a Timoshenko beam subjected to a partially distributed load was considered in this paper. The governing equation of fourth-order partial differential equation was reduced to a second-order Ordinary Differential Equation by normalizing the governing equation. The reduced second-order equation was further reduced to a first order ordinary differential system and was solved using fourth-order Runge-Kunta Method. The deflection for various parameters of the beam was considered and was plotted against x. It is observed that the vibration of the beam initially moves in a steady state before deflecting and the deflected amplitudeincreases as the Shear modulus, distance covered by the load, Mass of the load, Shear coefficient but decreases as the length of the load, the coefficient of the Shear foundation increases.
Keywords: Vibration; Timoshenko; Distributed partially; Shear coefficient; Shear foundation